Anisotropic Redox on Pristine Graphene - Akshat R. Saraf; Jay Min Lim; Ravi F. Saraf (Advanced Materials Interfaces)
Abstract Chemically modified graphene is an attractive electrode material for electrocatalysis, energy devices, and sensors, whereas pristine graphene is electrochemically passive. The remarkable anisotropic electrochemical nature of graphene is uncovered by π–π interaction, making pristine graphene more active than bare Au. The π–π stacking during redox reaction “dopes” the graphene, disrupting the passivating hydration layer, making it a facile electrochemical electrode. The structure during π–π stacking‐mediated redox of methylene blue (MB) is quantitatively measured by the differential reflectivity of a polarized laser on a ≈100 micron spot. The local redox reaction current varies over fourfold due to the orientation of the ≈10 micron size grains. The mosaic‐grain anisotropy on each spot shows local uniaxial orientation. The redox signal at the optimum orientation is over 2.5‐fold greater than that for bare Au on the same electrode. The redox signal is over fivefold greater at the edges of graphene compared bare Au. Remarkably, the π–π interaction increases chemical stability significantly, leading to negligible photo‐degradation at the approximate absorption wavelength of MB. The exclusive redox activity due to π–π interaction on pristine graphene adds to the toolbox of making exotic opto‐electrochemical electrode materials for electrocatalysis, sensing, and electronics.